Transcriptome and proteome profile of jejunum in chickens challenged with Salmonella Typhimurium revealed the effects of dietary bilberry anthocyanin on immune function - Zhang, Sheng; Wang, Qin; Ye, Jinling; Fan, Qiuli; Lin, Xiajing; Gou, Zhongyong; Azzam, Mahmoud M.; Wang, Yibing; Jiang, Shouqun (Frontiers in Microbiology, 2023)
The present study investigated the effects of bilberry anthocyanin (BA) on immune function when alleviating Salmonella Typhimurium (S. Typhimurium) infection in chickens. A total of 180 newly hatched yellow-feathered male chicks were assigned to 3 groups (CON, SI, SI+BA). Birds in CON and SI were fed a basal diet, and those in SI+BA were supplemented with 100 mg/kg BA for 18 days. Birds in SI and SI+BA received 0.5 mL suspension of S. Typhimurium (2×10 9 CFU/mL) by oral gavage at 14 and 16 days of age, and those in CON received equal volumes of sterile PBS. At d 18,(1) dietary BA alleviated weight loss of chickens caused by S. Typhimurium infection (P < 0.01). ( 2) Supplementation with BA reduced the relative weight of the bursa of Fabricius (P < 0.01) and jejunal villus height (P < 0.05), and increased the number of goblet cells (P < 0.01) and the expression of MUC2 (P < 0.05) in jejunal mucosa, compared with birds in SI. (3) Supplementation with BA decreased (P < 0.05) the